2005
DOI: 10.1073/pnas.0501581102
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the mechanical unfolding of ubiquitin

Abstract: The unfolding behavior of ubiquitin under the influence of a stretching force recently was investigated experimentally by single-molecule constant-force methods. Many observed unfolding traces had a simple two-state character, whereas others showed clear evidence of intermediate states. Here, we use Monte Carlo simulations to investigate the force-induced unfolding of ubiquitin at the atomic level. In agreement with experimental data, we find that the unfolding process can occur either in a single step or thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
77
6

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 38 publications
18
77
6
Order By: Relevance
“…Unlike classical unfolding experiments using chemicals or large temperature jumps, the mechanical unfolding of proteins is a highly localized process mainly involving the rupture of a few key hydrogen bonds within the structure of the protein native state, which constitutes the crucial structural motif that provides the protein with mechanical stability (41). In the case of the ubiquitin protein, the mechanical clamp is placed between the ␤1-␤5 sheets (42). After the rupture of this mechanical clamp, which constitutes the major energy barrier for unfolding, the protein extends up to almost its contour length without any extra enthalpic energy cost.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike classical unfolding experiments using chemicals or large temperature jumps, the mechanical unfolding of proteins is a highly localized process mainly involving the rupture of a few key hydrogen bonds within the structure of the protein native state, which constitutes the crucial structural motif that provides the protein with mechanical stability (41). In the case of the ubiquitin protein, the mechanical clamp is placed between the ␤1-␤5 sheets (42). After the rupture of this mechanical clamp, which constitutes the major energy barrier for unfolding, the protein extends up to almost its contour length without any extra enthalpic energy cost.…”
Section: Discussionmentioning
confidence: 99%
“…In atomic force spectroscopic studies of the elastomeric protein ubiquitin, the β-strands 1-5 serve as the force clamp under shear loading. Steered molecular dynamics (SMD) simulations (2, 4) showed that the shear loading force needs to break all four backbone hydrogen bonds (bbHBs) between the parallel β-strands 1-5 of ubiquitin in order to trigger protein unfolding (1,(5)(6)(7)(8). In SMD simulations of I27, Lu and Schulten observed that in the early stages of the pulling process individual bbHBs occasionally break and quickly reform, due to thermal fluctuations.…”
mentioning
confidence: 99%
“…The same model has also been used to study the mechanical unfolding of ubiquitin [16,17], a protein with 76 amino acids. The unfolding behavior of Fig.…”
Section: Mechanical Unfolding Of Ubiquitinmentioning
confidence: 99%
“…The simulations of the mechanical unfolding of ubiquitin were carried out at constant force [16]. As in the constant-force experiments [72], the forces acted on the chain ends.…”
Section: Mechanical Unfolding Of Ubiquitinmentioning
confidence: 99%
See 1 more Smart Citation